Silicone sealant and its preparation method and application, photovoltaic module

By using a specific proportion of graphene oxide and other components in silicone sealants, a complex anti-permeability diffusion path is formed, which solves the problem of insufficient anti-salt spray performance of traditional sealants in high salt spray environments, achieves higher hardness, tensile strength and anti-salt spray performance, and extends the service life of photovoltaic modules.

CN118480328BActive Publication Date: 2025-04-25TRINA SOLAR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410577532.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-04-25
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

Traditional silicone sealants cannot effectively block salt spray from entering the solar cell in high salt spray environment, resulting in chemical corrosion and electrical contact damage of solar cell cells, reducing the electrical performance of the components.

Method used

An organic silicone sealant including end-hydroxy polydimethylsiloxane, calcium carbonate, white carbon black, graphene oxide, crosslinking agent, coupling agent and catalyst is used to form a complex anti-permeability diffusion path and improve anti-salt spray performance by controlling the average sheet diameter of graphene oxide and the mass ratio to end-hydroxy polydimethylsiloxane.

Benefits of technology

It effectively improves the anti-salt spray performance of silicone sealants, while ensuring high hardness, tensile strength and elongation of break, as well as good shear strength and bonding performance, and extends the service life of offshore photovoltaic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to an organic silicon sealant and its preparation method and application, and a photovoltaic module. The organic silicon sealant comprises the following components by weight: 40-60 parts of terminal hydroxyl polydimethylsiloxane, 30-50 parts of calcium carbonate, 1-5 parts of white carbon black, 5-17 parts of graphene oxide, 3-6 parts of a cross-linking agent, 0.5-3 parts of a coupling agent, and 0.05-0.3 parts of a catalyst; wherein the average sheet diameter of the graphene oxide is 20 μm-40 μm, and the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane is (0.1-0.4):1. Using end-hydroxy polydimethylsiloxane as the base glue, combined with a specific proportion of fillers such as calcium carbonate, white carbon black, and graphene oxide, under the action of cross-linking agent, coupling agent and catalyst, utilizing the two-dimensional layer structure of graphene oxide, and controlling the average sheet diameter and addition ratio of graphene oxide, the salt spray resistance of silicone sealant can be effectively improved, while ensuring that the hardness, tensile strength and elongation at break of silicone sealant are high, as well as the shear strength and good bonding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to an organic silicon sealant and a preparation method and application thereof, and a photovoltaic module. Background Art

[0002] Solar photovoltaic power generation is a technology that uses the photovoltaic effect of semiconductor interfaces to directly convert light energy into electrical energy. With the sustainable development of human economy and society, the requirements for energy and environmental protection are getting higher and higher, and solar photovoltaic power generation is getting more and more attention. The core component of solar photovoltaic power generation is the solar cell. The solar cell itself has defects such as thinness, brittleness, and easy oxidation. It is easy to cause permanent damage when exposed to natural environments such as air and rain. Silicone sealant has high and low temperature resistance, weather resistance and good bonding properties, and is suitable for protective sealing of solar cell modules. In recent years, there are more and more photovoltaic offshore projects, which are facing a high salt fog environment. Once chloride ions and sodium ions enter the interior of the solar cell, the aluminum, lead oxide and silver on the front of the solar cell will undergo severe chemical corrosion, resulting in the destruction of the electrical contact of the solar cell, thereby reducing the electrical performance of the module, and may even cause the module to fail. However, the salt spray resistance of traditional silicone sealants is poor, and it cannot effectively prevent salt spray from entering the interior of the solar cell.

[0003] Therefore, it is necessary to improve the traditional technology. Summary of the invention

[0004] Based on this, the present application provides a silicone sealant with high tensile strength and good salt spray resistance, as well as a preparation method and application thereof, and a photovoltaic module.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] The first aspect of the present application provides a silicone sealant, which comprises the following components, by weight: 40 to 60 parts of terminal hydroxyl polydimethylsiloxane, 30 to 50 parts of calcium carbonate, 1 to 5 parts of white carbon black, 5 to 17 parts of graphene oxide, 3 to 6 parts of a cross-linking agent, 0.5 to 3 parts of a coupling agent and 0.05 to 0.3 parts of a catalyst; wherein the average flake diameter of the graphene oxide is 20 μm to 40 μm, and the mass ratio of the graphene oxide to the terminal hydroxyl polydimethylsiloxane is (0.1 to 0.4):1.

[0007] In some of the embodiments, the silicone sealant includes the following components, measured by weight: 40-50 parts of terminal hydroxyl polydimethylsiloxane, 35-45 parts of calcium carbonate, 2-5 parts of white carbon black, 5-15 parts of graphene oxide, 3-6 parts of cross-linking agent, 1-2 parts of coupling agent and 0.05-0.2 parts of catalyst.

[0008] In some of the embodiments, in the silicone sealant, the average flake diameter of the graphene oxide is 20 μm to 35 μm.

[0009] In some of the embodiments, in the silicone sealant, the mass ratio of the graphene oxide to the hydroxy-terminated polydimethylsiloxane is (0.15-0.375):1.

[0010] In some of the embodiments, in the silicone sealant, the viscosity of the hydroxy-terminated polydimethylsiloxane is 10000 mPa·s to 50000 mPa·s.

[0011] In some embodiments, in the silicone sealant, the specific surface area of ​​the white carbon black is 150 m 2 / g~250m 2 / g.

[0012] In some of the embodiments, in the silicone sealant, the average particle size of the calcium carbonate is 60 nm to 100 nm.

[0013] In some of the embodiments, in the silicone sealant, the crosslinking agent includes at least one of methyl tributylacetoximate silane, vinyl tributylacetoximate silane and tetrabutyl tributylacetoximate silane.

[0014] In some embodiments, in the silicone sealant, the coupling agent satisfies at least one of the following characteristics:

[0015] (1) The coupling agent includes at least one of aminosilane and aminosilane oligomer;

[0016] (2) The coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and bisaminosilane oligomer.

[0017] In some embodiments, in the silicone sealant, the catalyst satisfies at least one of the following characteristics:

[0018] (1) The catalyst includes an organotin catalyst;

[0019] (2) The catalyst includes at least one of dibutyltin dilaurate, stannous octoate and dibutyltin diceneodecanoate.

[0020] The second aspect of the present application provides a method for preparing an organosilicon sealant, comprising the following steps:

[0021] Providing raw materials according to the components of the above-mentioned organosilicon sealant;

[0022] The organosilicon sealant is prepared by mixing and stirring terminal hydroxyl polydimethylsiloxane, calcium carbonate, white carbon black, graphene oxide, a crosslinking agent, a coupling agent and a catalyst.

[0023] The third aspect of the present application provides the use of the above-mentioned silicone sealant in sealing photovoltaic modules.

[0024] A fourth aspect of the present application provides a photovoltaic module comprising the above-mentioned silicone sealant.

[0025] Compared with the prior art, the organic silicone sealant of the present application has the following beneficial effects:

[0026] The organic silicone sealant of the present application uses terminal hydroxyl polydimethylsiloxane as a base glue, and is mixed with fillers such as calcium carbonate, white carbon black, and graphene oxide in a specific proportion. Under the action of a cross-linking agent, a coupling agent, and a catalyst, the two-dimensional sheet structure of graphene oxide is utilized, and the average sheet diameter of graphene oxide and the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane are controlled to form a complex anti-penetration diffusion path, effectively reducing the permeability of chloride ions and sodium ions to the organic silicone sealant, thereby effectively improving the anti-salt spray performance of the organic silicone sealant, while ensuring that the hardness, tensile strength, and elongation at break of the organic silicone sealant are high, as well as the shear strength is high and the bonding performance is good.

[0027] The organosilicon sealant of the present application is used for encapsulating photovoltaic modules, which can effectively improve the hardness, tensile strength and elongation at break of photovoltaic modules, effectively solve the problem that solar cells are easily damaged due to their thinness and brittleness, and effectively improve the anti-salt spray performance of photovoltaic modules, especially effectively extend the service life of offshore photovoltaic products. DETAILED DESCRIPTION

[0028] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0029] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0031] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0032] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0033] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0034] An embodiment of the present application provides a silicone sealant, which includes the following components in parts by weight: 40-60 parts of terminal hydroxyl polydimethylsiloxane, 30-50 parts of calcium carbonate, 1-5 parts of white carbon black, 5-17 parts of graphene oxide, 3-6 parts of a cross-linking agent, 0.5-3 parts of a coupling agent and 0.05-0.3 parts of a catalyst; wherein the average flake diameter of the graphene oxide is 20 μm-40 μm, and the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane is (0.1-0.4):1.

[0035] The organic silicone sealant of the present application uses terminal hydroxyl polydimethylsiloxane as a base glue, and is mixed with fillers such as calcium carbonate, white carbon black, and graphene oxide in a specific proportion. Under the action of a cross-linking agent, a coupling agent, and a catalyst, the two-dimensional sheet structure of graphene oxide is utilized, and the average sheet diameter of graphene oxide and the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane are controlled to form a complex anti-penetration diffusion path, effectively reducing the permeability of chloride ions and sodium ions to the organic silicone sealant, thereby effectively improving the anti-salt spray performance of the organic silicone sealant, while ensuring that the hardness, tensile strength, and elongation at break of the organic silicone sealant are high, as well as the shear strength is high and the bonding performance is good.

[0036] The organosilicon sealant of the present application is used for encapsulating photovoltaic modules, which can effectively improve the hardness, tensile strength and elongation at break of photovoltaic modules, effectively solve the problem that solar cells are easily damaged due to their thinness and brittleness, and effectively improve the anti-salt spray performance of photovoltaic modules, especially effectively extend the service life of offshore photovoltaic products.

[0037] It can be understood that the silicone sealant, by weight, includes but is not limited to 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts, 58 parts, and 60 parts of terminal hydroxyl polydimethylsiloxane; includes but is not limited to 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, and 50 parts of calcium carbonate; includes but is not limited to 1 part, 2 parts, 3 parts, 4 parts, and 5 parts of white carbon black; and includes but is not limited to 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts; cross-linking agents include but are not limited to 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts; coupling agents include but are not limited to 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts; catalysts include but are not limited to 0.05 parts, 0.1 parts, 0.05 parts, 0.2 parts, 0.25 parts, 0.3 parts; in some examples, any two of these point values ​​can be within the range formed by the end values, the same below.

[0038] In some of the examples, the silicone sealant includes the following components, measured by weight: 40-50 parts of terminal hydroxyl polydimethylsiloxane, 35-45 parts of calcium carbonate, 2-5 parts of white carbon black, 5-15 parts of graphene oxide, 3-6 parts of cross-linking agent, 1-2 parts of coupling agent and 0.05-0.2 parts of catalyst.

[0039] In some of the examples, the silicone sealant includes the following components, measured by weight: 40-50 parts of terminal hydroxyl polydimethylsiloxane, 40-42 parts of calcium carbonate, 2-5 parts of white carbon black, 8-15 parts of graphene oxide, 4-5 parts of cross-linking agent, 1-1.5 parts of coupling agent and 0.08-0.1 parts of catalyst.

[0040] It is understood that the average sheet diameter of graphene oxide includes but is not limited to 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, and 40 μm.

[0041] In some of these examples, the average flake size of graphene oxide in silicone sealants is 30 μm to 40 μm.

[0042] It can be understood that the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane includes but is not limited to 0.1:1, 0.12:1, 0.15:1, 0.16:1, 0.18:1, 0.2:1, 0.22:1, 0.25:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.35:1, 0.36:1, and 0.375:1.

[0043] In some of these examples, the mass ratio of graphene oxide to hydroxy-terminated polydimethylsiloxane in the silicone sealant is (0.16~0.375):1.

[0044] In some of these examples, the mass ratio of graphene oxide to hydroxy-terminated polydimethylsiloxane in the silicone sealant is (0.16~0.3):1.

[0045] It can be understood that hydroxy-terminated polydimethylsiloxane refers to polydimethylsiloxane with hydroxyl groups at both ends. However, single-terminated hydroxyl groups cannot form a cross-linked network structure after cross-linking, which is not conducive to improving tensile strength and salt spray resistance.

[0046] In some of these examples, the viscosity of the hydroxy-terminated polydimethylsiloxane in the silicone sealant is 10,000 mPa·s to 50,000 mPa·s.

[0047] It can be understood that the viscosity of the terminal hydroxyl polydimethylsiloxane includes but is not limited to 10000 mPa·s, 15000 mPa·s, 20000 mPa·s, 25000 mPa·s, 30000 mPa·s, 35000 mPa·s, 40000 mPa·s, 45000 mPa·s, and 50000 mPa·s.

[0048] In some of these examples, the viscosity of the hydroxy-terminated polydimethylsiloxane in the silicone sealant is 10,000 mPa·s to 30,000 mPa·s.

[0049] In some of these examples, the surface area of ​​silica in silicone sealants is 150 m 2 / g~250 m 2 / g.

[0050] It is understood that the specific surface area of ​​white carbon black includes but is not limited to 150 m 2 / g, 160 m 2 / g, 170 m 2 / g, 180m 2 / g, 190 m 2 / g, 200 m 2 / g, 210 m 2 / g, 220 m 2 / g, 230 m 2 / g, 240 m 2 / g, 250 m 2 / g.

[0051] In some of these examples, the average particle size of calcium carbonate in silicone sealants is 60 nm to 100 nm.

[0052] It is understood that the average particle size of calcium carbonate includes but is not limited to 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.

[0053] In some of the examples, in the silicone sealant, the calcium carbonate includes at least one of light calcium carbonate, heavy calcium carbonate, and nano calcium carbonate.

[0054] It can be understood that in some of the examples, the crosslinking agent includes but is not limited to at least one of methyltributylacetonatomosilane, vinyltributylacetonatomosilane, tetrabutylketonemosilane, propyltributylacetonatomosilane, phenyltributylacetonatomosilane, methyltriacetonemosilane and vinyltriacetonemosilane.

[0055] In some of the examples, in the silicone sealant, the crosslinking agent includes at least one of methyltributylacetoximate silane, vinyltributylacetoximate silane and tetrabutylketoxime silane.

[0056] In some of the examples, in the silicone sealant, the crosslinking agent includes at least two of methyl tributylacetoximate silane, vinyl tributylacetoximate silane and tetrabutyl tributylacetoximate silane.

[0057] In some of the examples, in the silicone sealant, the crosslinking agent includes a mixture of methyltributylacetoximate silane and vinyltributylacetoximate silane, or the crosslinking agent includes a mixture of tetrabutylketoxime silicon and vinyltributylacetoximate silane.

[0058] Furthermore, the mass ratio of methyl tributylidene oxime silane to vinyl tributylidene oxime silane is (2-3):1.

[0059] It can be understood that the mass ratio of methyl tributylidene oxime silane to vinyl tributylidene oxime silane includes but is not limited to 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, and 3:1.

[0060] Furthermore, the mass ratio of tetrabutyl ketoxime silicon to vinyltributyl ketoxime silane is (1~3):1.

[0061] It will be appreciated that the mass ratio of tetrabutyl ketoxime silicon to vinyltributyl ketoxime silane includes but is not limited to 1:1, 1.1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, and 3:1.

[0062] In some of the examples, in the silicone sealant, the coupling agent includes at least one of aminosilane and aminosilane oligomer.

[0063] In some of the examples, in the silicone sealant, the aminosilane includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0064] In some of the examples, in the silicone sealant, the aminosilane oligomer includes a bisaminosilane oligomer. Further, the aminosilane oligomer includes but is not limited to at least one of Evonik 1146, Jianghan AP1231 and New Blue Sky LT-1146.

[0065] It is understood that the coupling agent may include only one of aminosilane and aminosilane oligomer, or may include both.

[0066] In some of the examples, in the silicone sealant, the coupling agent includes both aminosilane and aminosilane oligomer.

[0067] In some of these examples, the mass ratio of aminosilane to aminosilane oligomer in the silicone sealant is (1~5):1.

[0068] It is understood that the mass ratio of aminosilane to aminosilane oligomer includes, but is not limited to, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, and 3:1.

[0069] In some of these examples, in silicone sealants, the catalyst includes an organotin-based catalyst.

[0070] In some of the examples, in the silicone sealant, the catalyst includes at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin dineodecanoate.

[0071] The components of the above-mentioned silicone sealant interact with each other in a specific ratio, so that the silicone sealant has good salt spray resistance, high hardness, tensile strength and elongation at break, high shear strength and good bonding performance.

[0072] An embodiment of the present application provides a method for preparing an organosilicon sealant, comprising the following steps:

[0073] Providing raw materials according to the components of the above-mentioned organosilicon sealant;

[0074] The end-hydroxy polydimethylsiloxane, calcium carbonate, white carbon black, graphene oxide, a cross-linking agent, a coupling agent and a catalyst are mixed and stirred to prepare an organic silicone sealant.

[0075] It can be understood that the preparation method of the organosilicon sealant provided in the present application can prepare the above-mentioned organosilicon sealant, that is, the organosilicon sealant prepared by the preparation method of the organosilicon sealant provided in the present application has good salt spray resistance, and at the same time has high hardness, tensile strength and elongation at break, as well as high shear strength and good bonding performance. Further, the above-mentioned organosilicon sealant can be prepared by the preparation method of the organosilicon sealant provided in the present application, but the preparation of the above-mentioned organosilicon sealant is not limited to the preparation method of the organosilicon sealant provided in the present application. It can also be understood that the characteristics of the above-mentioned organosilicon sealant and the characteristics in the preparation method of the organosilicon sealant provided in the present application can be mutually applicable.

[0076] In some of the examples, the method for preparing the silicone sealant includes the following steps:

[0077] Step S10: mixing terminal hydroxyl polydimethylsiloxane, calcium carbonate, white carbon black and graphene oxide for a first stirring to prepare a base material.

[0078] In some examples, in step S10 , first stirring is performed under vacuum conditions.

[0079] Furthermore, the vacuum degree of the first stirring is ≤-0.095 Mpa.

[0080] In some examples, in step S10, the temperature of the first stirring is 100°C to 110°C.

[0081] It can be understood that the temperature of the first stirring includes but is not limited to 100°C, 102°C, 105°C, 108°C, and 110°C.

[0082] In some examples, in step S10, the first stirring time is 1 h to 3 h.

[0083] It can be understood that the first stirring time includes but is not limited to 1 h, 2 h, and 3 h.

[0084] It can be understood that the base material is obtained by cooling after the first stirring.

[0085] In some examples, in step S10 , the first stirring is performed in a kneader.

[0086] Step S20: Mix the prepared base material and the cross-linking agent and perform a second stirring to prepare an intermediate material.

[0087] In some examples, in step S20, the second stirring time is 20 min to 40 min.

[0088] It can be understood that the second stirring time includes but is not limited to 20 min, 25 min, 30 min, 35 min, and 40 min.

[0089] In some of the examples, in step S20, the second mixing is performed in a planetary mixer.

[0090] Step S30: mixing the coupling agent and the catalyst with the intermediate material for a third stirring to prepare an organic silicone sealant.

[0091] In some examples, in step S30 , the third stirring is performed under vacuum conditions.

[0092] Furthermore, the vacuum degree of the third stirring is ≤-0.095 Mpa.

[0093] In some examples, in step S30, the third stirring time is 20 min to 40 min.

[0094] It can be understood that the third stirring time includes but is not limited to 20 min, 25 min, 30 min, 35 min, and 40 min.

[0095] In some of the examples, in step S30, the third mixing is performed in a planetary mixer.

[0096] It can be understood that in step S30, the coupling agent and the catalyst can be directly added to the intermediate material obtained in step S20.

[0097] One embodiment of the present application provides the use of the above-mentioned organosilicon sealant or the organosilicon sealant prepared by the above-mentioned preparation method in sealing a photovoltaic module. Another embodiment of the present application provides a photovoltaic module, including the above-mentioned organosilicon sealant or the organosilicon sealant prepared by the above-mentioned preparation method.

[0098] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0099] The silicone sealants of the following embodiments and comparative examples were prepared as follows:

[0100] (1) Adding the base rubber (hydroxy-terminated polydimethylsiloxane) and fillers (calcium carbonate, white carbon black, graphene oxide) into a kneader one by one, stirring for 1 h to 3 h at a temperature of 100°C to 110°C and a vacuum degree of no more than -0.095 MPa, and cooling to obtain a base material;

[0101] (2) Add the base material and cross-linking agent prepared in step (1) into a planetary mixer and stir to react for 20 min to 40 min;

[0102] (3) Continue to add coupling agent and catalyst into the planetary machine, evacuate the mixture, and stir the mixture at the same time. After the vacuum degree reaches -0.095 MPa, continue stirring for 20 min to 40 min to obtain a silicone sealant.

[0103] Example 1

[0104] The components of silicone sealant are as follows by weight:

[0105] 45 parts of hydroxy-terminated polydimethylsiloxane, viscosity 20000 mPa·s;

[0106] 42 parts of calcium carbonate, nano calcium carbonate with an average particle size of 60 nm;

[0107] 3 parts of white carbon black, with a specific surface area of ​​150 m 2 / g;

[0108] 10 parts of graphene oxide, average flake diameter 30 μm;

[0109] 4 parts of a crosslinking agent, including 2.5 parts of tetrabutyl ketoxime silane and 1.5 parts of vinyl tributyketoxime silane;

[0110] 1 part of coupling agent, including 0.8 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.5 parts of amino coupling agent oligomer Evonik 1146; and

[0111] Catalyst 0.08 parts, dibutyltin dilaurate.

[0112] Example 2

[0113] The components of silicone sealant are as follows by weight:

[0114] 50 parts of hydroxy-terminated polydimethylsiloxane, viscosity 30000 mPa·s;

[0115] 40 parts of calcium carbonate, nano calcium carbonate with an average particle size of 100 nm;

[0116] 2 parts of white carbon black, with a specific surface area of ​​150 m 2 / g;

[0117] 8 parts of graphene oxide, average flake diameter 35 μm;

[0118] 5 parts of a crosslinking agent, including 3.5 parts of methyl tributylacetoximate silane and 1.5 parts of vinyl tributylacetoximate silane;

[0119] 1.5 parts of coupling agent, including 1 part of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.8 parts of amino coupling agent oligomer; and

[0120] Catalyst 0.12 parts, dibutyltin dilaurate.

[0121] Example 3

[0122] The components of silicone sealant are as follows by weight:

[0123] 40 parts of hydroxy-terminated polydimethylsiloxane, viscosity 10000 mPa·s;

[0124] 40 parts of calcium carbonate, nano calcium carbonate with an average particle size of 80 nm;

[0125] 5 parts of white carbon black, with a specific surface area of ​​250 m 2 / g;

[0126] 15 parts of graphene oxide, average flake diameter 20 μm;

[0127] 4 parts of a crosslinking agent, including 3 parts of tetrabutyl ketoxime silane and 1 part of vinyl tributyketoxime silane;

[0128] 1.2 parts of coupling agent, including 0.5 parts of γ-aminopropyltriethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and 0.2 parts of amino coupling agent oligomer; and

[0129] Catalyst 0.1 parts, dibutyltin dilaurate.

[0130] Example 4

[0131] The method is substantially the same as Example 1, except that the average sheet diameter of graphene oxide in Example 4 is 40 μm.

[0132] Example 5

[0133] The method is substantially the same as Example 1, except that the average sheet diameter of graphene oxide in Example 5 is 20 μm.

[0134] Example 6

[0135] It is basically the same as Example 2, except that the number of parts of graphene oxide is 5 parts, the number of parts of calcium carbonate is 43 parts, the total number of parts of graphene oxide, calcium carbonate and white carbon black in Example 6 is the same as the total number of parts of graphene oxide, calcium carbonate and white carbon black in Example 2; the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane is 0.1:1.

[0136] Example 7

[0137] It is basically the same as Example 2, except that the number of parts of graphene oxide is 15 parts, the number of parts of calcium carbonate is 33 parts, the total number of parts of graphene oxide, calcium carbonate and white carbon black in Example 7 is the same as the total number of parts of graphene oxide, calcium carbonate and white carbon black in Example 2; the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane is 0.3:1.

[0138] Comparative Example 1

[0139] It is basically the same as Example 1, except that graphene oxide is not added, and the number of parts of calcium carbonate is 50 parts, the number of parts of white carbon black is 5 parts, and the total number of parts of calcium carbonate and white carbon black in Comparative Example 1 is the same as the total number of parts of graphene oxide, calcium carbonate and white carbon black in Example 1; the components of the silicone sealant are as follows by weight:

[0140] 45 parts of hydroxy-terminated polydimethylsiloxane, viscosity 20000 mPa·s;

[0141] 50 parts of calcium carbonate, nano calcium carbonate with an average particle size of 60 nm;

[0142] 5 parts of white carbon black, with a specific surface area of ​​150 m 2 / g;

[0143] 4 parts of a crosslinking agent, including 2.5 parts of tetrabutyl ketoxime silane and 1.5 parts of vinyl tributyketoxime silane;

[0144] 1 part of a coupling agent, including 0.8 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.5 parts of an amino coupling agent oligomer; and

[0145] Catalyst 0.08 parts, dibutyltin dilaurate.

[0146] Comparative Example 2

[0147] It is basically the same as Example 2, except that the average sheet diameter of graphene oxide in Comparative Example 2 is 80 μm.

[0148] Comparative Example 3

[0149] The mass ratio of graphene oxide to hydroxy-terminated polydimethylsiloxane is about 0.05:1; by weight, the components of the silicone sealant are as follows:

[0150] 54 parts of hydroxy-terminated polydimethylsiloxane, viscosity 20000 mPa·s;

[0151] 40 parts of calcium carbonate, nano calcium carbonate with an average particle size of 80 nm;

[0152] 1 part of white carbon black, with a specific surface area of ​​200 m 2 / g;

[0153] Graphene oxide 2.8 parts, average flake diameter 30 μm;

[0154] 4.5 parts of a cross-linking agent, including 0.5 parts of methyl tributylacetoximate silane, 3 parts of tetrabutyl ketone oxime silane, and 1 part of vinyl tributylacetoximate silane;

[0155] 1.3 parts of coupling agent, including 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.8 parts of amino coupling agent oligomer; and

[0156] Catalyst 0.1 parts, dibutyltin dilaurate.

[0157] Comparative Example 4

[0158] It is basically the same as Example 1, except that the mass ratio of graphene oxide to terminal hydroxyl polydimethylsiloxane is about 0.6:1, that is, the addition amount of graphene oxide is 27 parts, and the parts of other components remain unchanged.

[0159] Comparative Example 5

[0160] It is basically the same as Example 1, except that the graphene oxide in Example 1 is replaced by graphene of equal mass.

[0161] Comparative Example 6

[0162] It is basically the same as Example 1, except that no white carbon black is added and the amount of calcium carbonate is 45 parts.

[0163] The components of the organic silicon sealant provided in each embodiment and comparative example are shown in Table 1.

[0164] Table 1

[0165]

[0166] The organosilicon sealants provided in the embodiments and comparative examples were subjected to the following performance tests:

[0167] Pass GB / T 531 test on the hardness of silicone;

[0168] Pass GB / T 528 test on the tensile strength and elongation at break of silicone rubber;

[0169] Passed GB / T 7124 test on the shear strength of silicone (anodized aluminum profiles);

[0170] The salt spray corrosion resistance of silicone was tested according to GB / T 1771-2007; the sample preparation and experimental process of the salt spray test were as follows: the test samples were all 150 mm×100 mm×1 mm steel plates, the surface was degreased with solvent and polished with sandpaper, the silicone sealant was applied on the steel plate, and the silicone adhesive was evenly applied on the front and back surfaces and sides of the steel plate using a thickness controller so that the silicone adhesive completely covered the steel plate. The thickness of the silicone adhesive was controlled at (150±10) μm, and the salt spray test was carried out after curing for 14 days under standard test conditions (temperature (23±2)℃, relative humidity (50±5)%), and attention was paid to ensure that the silicone was completely cured.

[0171] The test results are shown in Table 2.

[0172] Table 2

[0173]

[0174] It can be seen from Table 2 that, compared with the comparative example, the organosilicon sealant prepared in each embodiment has higher hardness, tensile strength and elongation at break, higher shear strength and better bonding performance; at the same time, it has better anti-salt spray corrosion performance, and the surface condition of the steel plate is good under the 1000h salt spray test, especially the surface condition of the steel plate of Embodiments 1 to 4 and Embodiment 7 is still good under the 1500h salt spray test. In comparative example 1, graphene oxide was not used in combination with other components, and severe rust appeared on the surface of the steel plate under a 500-hour salt spray test; in comparative example 2, graphene oxide of a specific sheet diameter was not used, and its tensile strength, elongation at break and shear strength decreased to varying degrees, which could not meet the basic use requirements of photovoltaic modules; in comparative example 3, an inappropriate addition ratio of graphene oxide would affect the salt spray corrosion resistance of the silicone sealant; in comparative example 4, excessive graphene oxide was used, resulting in different degrees of reduction in its hardness, tensile strength, elongation at break and shear strength, which could not meet the basic use requirements of photovoltaic modules; this shows that when the addition ratio of graphene oxide is inappropriate, tensile strength and salt spray resistance cannot be taken into account; in comparative example 5, graphene oxide was not used, but graphene of equal mass was used, resulting in a decrease in the electrical insulation performance of the system, which poses a risk in actual use; in comparative example 6, white carbon black was not used in combination with other components, and its tensile strength, elongation at break and shear strength decreased to varying degrees, which could not meet the basic use requirements of photovoltaic modules.

[0175] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0176] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A silicone sealant, characterized in that: The invention comprises the following components by weight: 40 to 60 parts of terminal hydroxyl polydimethylsiloxane, 30 to 50 parts of calcium carbonate, 1 to 5 parts of white carbon black, 5 to 17 parts of graphene oxide, 3 to 6 parts of a cross-linking agent, 0.5 to 3 parts of a coupling agent and 0.05 to 0.3 parts of a catalyst; wherein the average sheet diameter of the graphene oxide is 20 μm to 40 μm, the mass ratio of the graphene oxide to the terminal hydroxyl polydimethylsiloxane is (0.1 to 0.4):1, and the specific surface area of ​​the white carbon black is 150 m 2 / g~250m 2 / g, and the average particle size of the calcium carbonate is 60nm-100nm.

2. The organic silicon sealant according to claim 1, characterized in that: The composition comprises the following components by weight: 40-50 parts of terminal hydroxyl polydimethylsiloxane, 35-45 parts of calcium carbonate, 2-5 parts of white carbon black, 5-15 parts of graphene oxide, 3-6 parts of cross-linking agent, 1-2 parts of coupling agent and 0.05-0.2 parts of catalyst.

3. The organic silicon sealant according to claim 1, characterized in that: The average sheet diameter of the graphene oxide is 20 μm to 35 μm.

4. The organic silicon sealant according to claim 1, characterized in that: The mass ratio of the graphene oxide to the terminal hydroxyl polydimethylsiloxane is (0.15-0.375):

1.

5. The organic silicon sealant according to claim 1, characterized in that: The viscosity of the terminal hydroxyl polydimethylsiloxane is 10000 mPa·s to 50000 mPa·s.

6. The organic silicon sealant according to claim 1, characterized in that: The specific surface area of ​​the white carbon black is 150 m 2 / g.

7. The organic silicon sealant according to claim 1, characterized in that: The average particle size of the calcium carbonate is 100 nm.

8. The organic silicon sealant according to any one of claims 1 to 7, characterized in that: The crosslinking agent includes at least one of methyltributylacetoximosilane, vinyltributylacetoximosilane and tetrabutylketoximesilane.

9. The organic silicon sealant according to any one of claims 1 to 7, characterized in that: The coupling agent includes at least one of aminosilane and aminosilane oligomer.

10. The organic silicon sealant according to claim 9, characterized in that: The coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and bisaminosilane oligomer.

11. The organic silicon sealant according to any one of claims 1 to 7, characterized in that: The catalyst includes an organotin catalyst.

12. The organic silicon sealant according to claim 11, characterized in that: The catalyst includes at least one of dibutyltin dilaurate, stannous octoate and dibutyltin diceneodecanoate.

13. A method for preparing an organosilicon sealant, characterized in that: The following steps are involved: Providing raw materials according to the components of the organic silicon sealant according to any one of claims 1 to 12; The organosilicon sealant is prepared by mixing and stirring terminal hydroxyl polydimethylsiloxane, calcium carbonate, white carbon black, graphene oxide, a crosslinking agent, a coupling agent and a catalyst.

14. Use of the organosilicon sealant according to any one of claims 1 to 12 in sealing photovoltaic modules.

15. A photovoltaic module, characterized in that: The invention comprises the organic silicon sealant as claimed in any one of claims 1 to 12.

Citation Information

Patent Citations

  • Acid mist corrosion resistant two-component silicone structural adhesive and preparation method thereof

    CN116836677A